PEMASARAN TERNAK SAPI POTONG DI KABUPATEN OGAN KOMERING ILIR SUMATERA SELATAN - , JAKA SUMITRA; , Dr. Tri Anggraeni Kusumastuti, SP. MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was aimed to identify the marketing channels, calculate the marketing margins, estimate and heavy weight of cattle, gross margin of farmers, village traders, wholesalers, butchers and determine the marketing strategy policies. The research locations were selected by purposive sampling in three districts namely Lempuing, Lempuing Jaya and Mesuji Raya in Ogan Komering Ilir. The study was conducted from July to August 2011. The respondents were 60 farmers, 15 village traders, wholesalers and butchers each had five (5) respondents. The object were the weighting of cattle sold at farmers level, village traders, wholesalers each with 60 cattle (30 males and 30 females) and butchers with 30 males. The methods used were through surveys with direct observations and interviews with respondents and conducting the weighting of livestock. The analysis used descriptive analysis for the marketing margins and quantitative analysis, the t-test was used to compare the estimate and heavy weight of beef cattle. Further compare the gross margins of farmers, village traders, wholesalers and butchers, the one way ANOVA followed by Duncansâ Multiple Range Test (DMRT) was used. The results was obtained by three (3) marketing channels, the 1st channel was the farmer to butcher with two brokers, the 2nd channel from farmers to butcher with one broker and 3rd channel from farmers directly to the butcher. The first channel recorded a marketing margin of Rp 2,562,835,-/head and the 2nd channel recorded Rp. 930,979,-/head. No significant difference between the severe crush cattle and heavy weight was found. The gross margin had a significant difference (P â¤0.05) between the farmers (Rp. 873,833,-a/head) with village traders and butchers recording of (Rp 1,783,213,-b/head) and (Rp 3,256,898,-c/head) respectively, whereas there was no difference with wholesalers recording (Rp 326,736,-a/head). Marketing policy strategies to improve farmer gross margin through the selection of the most profitable marketing channels, pricing policies that determine the price of livestock standards and policies of the gross margin provides input and output prices are favorable farmers.